Priraščanje navadne smreke (Picea abies (L.) Karst.) in evropskega macesna (Larix decidua Mill.) na nekdanjih novinah v Koprivni v Karavankah - Golob, Janez (Acta silvae et ligni, 2021)
Based on previous measurements from 1962 to 2017 on forest research plots located on former slash-and-burn farming areas in the cadastral municipality of Koprivna, the diameter and height increment as well as volume increments of the two main tree species - spruce and larch - were calculated. These set-aside natural research plots have a smaller mean basal area diameter, but the number of trees is higher than in comparable managed forests. Due to the high-density of tree stands over the past thirty years, radial increment of spruce and larch has declined. To determine the influence of environmental factors on radial growth of spruce and larch, a dendrochronological analysis was conducted. According to the dendrochronological analysis of radial increment of trees, the number of years with a negative response has been higher since 1984.
Keywords: debelinski prirastek; dendrochronological analysis; dendrokronološka analiza; diameter increment; European larch; indeks gostote SDI; macesen; Norway spruce; raziskovalne ploskve; research plots; smreka; stand density index; volume increment; volumenski prirastek